GENERAL BOUNDARY-ELEMENT METHOD FOR UNSTEADY NONLINEAR HEAT TRANSFER PROBLEMS - Liao, Shi-Jun (Numerical heat transfer. Part B, Fundamentals, 1999)
The general boundary-element method (BEM) for strongly nonlinear problems proposed in \[1 - 3] is further applied to solve a two-dimensional (2D), unsteady, nonlinear heat transfer problem in the time domain, governed by the parabolic heat conduction equation with temperature-dependent thermal conductivity coefficients that are different in the x and y directions. This article shows that the general BEM is valid to solve even those nonlinear unsteady heat transfer problems whose governing equations do not contain any linear terms in the spatial derivatives. This demonstrates the validity and the great potential of the general BEM.